Urgent Virtual Eye Assessments During the COVID-19 Pandemic - Ma J; Issa M; Varma D; Ahmed IIK (Clinical Ophthalmology, 2022)
Jingyi Ma, Mariam Issa, Devesh Varma, Iqbal IK Ahmed Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, Ontario, CanadaCorrespondence: Iqbal IK Ahmed, Ophthalmology and Vision Sciences, University of Toronto, 2201 Bristol Circle, Suite 100, Oakville, Ontario, L6H 0J8, Canada, Tel +1 (905) 456-3937, Email ikeahmed@mac.comPurpose: We aimed to evaluate the effectiveness and safety of a virtual eye assessment triage system implemented in response to COVID-19.Patients and Methods: We conducted a retrospective cross-sectional study using a consecutive sample of all virtual assessments conducted from March 24 to June 7, 2020 at a single ophthalmology center in Toronto, ON, Canada. Visual acuity and smartphone photographs were uploaded to an electronic assessment website. All patients were virtually triaged to an email or phone consult. Patient outcomes and satisfaction were assessed with a quality assurance survey. Primary outcome measures were the incidence of unplanned additional in-person visits and changes in treatment.Results: We performed 1535 virtual assessments. Of the triage pathways, 15% received an email consult only and 85% received a phone consult. Subsequently, 15% required an in-person assessment, 3% were referred elsewhere, and 0.1% were sent to the emergency. Presentations were most commonly cornea (52%) and retina (25%). They were non-urgent in 68% of cases and no pharmacologic treatment was required for 49%. Of 397 patients that responded out of 653 patients surveyed, 4% had an unplanned additional visit to the emergency, after which two patients underwent urgent retinal surgery and one patient underwent urgent glaucoma surgery. Two patients (0.5%) had a minor change in treatment.Conclusion: As routine regular in-person visits were not possible during the COVID-19 lockdown, virtual eye assessments provided an opportunity to triage patients. Virtual assessments have the potential to reduce in-person visits, but caution must be exercised to not miss vision-threatening conditions.Keywords: virtual care, telemedicine, COVID-19, medical education